2002
DOI: 10.1103/physrevlett.88.075507
|View full text |Cite
|
Sign up to set email alerts
|

Random Packings of Frictionless Particles

Abstract: We conduct numerical simulations of random packings of frictionless particles at T = 0. The packing fraction where the pressure becomes nonzero is the same as the jamming threshold, where the static shear modulus becomes nonzero. The distribution of threshold packing fractions narrows, and its peak approaches random close packing as the system size increases. For packing fractions within the peak, there is no self-averaging, leading to exponential decay of the interparticle force distribution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

80
962
11
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 610 publications
(1,069 citation statements)
references
References 23 publications
80
962
11
3
Order By: Relevance
“…In both cases ∆Z goes to zero at jamming: ∆Z ∼ √ ∆φ [5,20,21]. A recent experiment aimed at testing this scaling, albeit in a system with friction, can be found in [22].…”
Section: Isostaticity and Marginally Connected Solidsmentioning
confidence: 99%
“…In both cases ∆Z goes to zero at jamming: ∆Z ∼ √ ∆φ [5,20,21]. A recent experiment aimed at testing this scaling, albeit in a system with friction, can be found in [22].…”
Section: Isostaticity and Marginally Connected Solidsmentioning
confidence: 99%
“…This model has been wellstudied and it is significantly different from our experimental system with respect to friction, gravity, and the fixed boundaries. We generate mechanically-stable packings via a standard conjugate-gradient method [40]. We then perform simulations for a fixed packing fraction and volume, and we analyze 20 mechanically-stable packings at each packing fraction φ.…”
Section: B Frictionless Simulationsmentioning
confidence: 99%
“…In Ref. [65] the authors showed that the presence of non-self-averaging alters the force distribution function P (F ), which we now consider. In foams and granular materials, P (F ) is measured as a distribution of interparticle normal forces [66,67].…”
Section: Average Force and Instantaneous Force Distribution Functmentioning
confidence: 99%